Microelectronics packaging handbook - Rymaszewski, Eugene J.; Klopfenstein, Alan G. (Chapman & Hall, 1997)
Provides the advances in microelectronics design methods, modeling tools, simulation techniques, and manufacturing procedures. This book discusses packages that meet the power, cooling, protection, and interconnection requirements of increasingly dense and fast microcircuitry.